2013
DOI: 10.1111/jcpp.12079
|View full text |Cite
|
Sign up to set email alerts
|

Social communication disorder outside autism? A diagnostic classification approach to delineating pragmatic language impairment, high functioning autism and specific language impairment

Abstract: Results provide empirical support for a conceptualisation of PLI as a developmental impairment distinguishable from HFA by absence of RRBIs and by the presence of expressive language difficulties. PI difficulties appear elevated in PLI compared with SLI, but may be less pervasive than in HFA. Findings are discussed with reference to the proposed new category of 'social communication disorder' in DSM-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 45 publications
(48 reference statements)
4
56
0
7
Order By: Relevance
“…Such deficits are likely to impact on the social use of language. Their profile is similar to children with a diagnosis of PLI in a recent study who were considered to meet criteria for SPCD (Gibson, Adams, Lockton, & Green, 2013;Norbury, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Such deficits are likely to impact on the social use of language. Their profile is similar to children with a diagnosis of PLI in a recent study who were considered to meet criteria for SPCD (Gibson, Adams, Lockton, & Green, 2013;Norbury, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, a field trial focusing on this disorder has not been done yet. Therefore, there seems to be much current confusion about the diagnosis of SCD [12,13]. Gibson et al [12] suggested that SCD is a developmental disorder outside ASD, but SCD does not belong to a group of ASD, but to a group of communication disorders in the textbook of DSM-5 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with ASD in the absence of ID may develop fluent language, but often with deficits in pragmatic aspects of language comprehension in addition to impaired use of language in social interaction. These milder forms of ID and ASD border on normal variation, and an additional category of pragmatic language impairment has been proposed for individuals who show the linguistic deficits characteristic of ASD but without the repetitive behaviors (Gibson et al 2013). Mild forms of ID and ASD appear to have a complex genetic basis, possibly with significant contributions from environmental influences (Gaugler et al 2014;van Bokhoven 2011).…”
Section: Intellectual Disability and Autism Spectrum Disordersmentioning
confidence: 99%